2010
DOI: 10.5021/ad.2010.22.1.21
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of 4-n-butylresorcinol 0.1% Cream for the Treatment of Melasma: A Randomized Controlled Split-face Trial

Abstract: Background: Melasma is a common acquired symmetrical hypermelanosis that occurs on sun-exposed areas, and it is frequently observed among women. Various treatment modalities have been tried, but none are completely satisfactory. 4-n-butylresorcinol, which is a resorcinol derivative that has an inhibitory effect on both tyrosinase and tyrosinase-related protein-1, was introduced in 1995 and it has received increasing attention as a new hypopigmenting agent. However, the hypopigmenting effect of 4-n-butylresorci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 12 publications
1
38
0
Order By: Relevance
“…In a randomized, double-blind, vehicle-controlled, split-face study, the use of 0.1% 4nBR cream significantly reduced lesional MI compared with control at week 4 and week 8. 6 Lesional MI decreased by −3.43% at week 4 and −4.87% at week 8 from the baseline. Mild irritation was observed in 10% of the patients at week 4 and self-limited at week 8.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…In a randomized, double-blind, vehicle-controlled, split-face study, the use of 0.1% 4nBR cream significantly reduced lesional MI compared with control at week 4 and week 8. 6 Lesional MI decreased by −3.43% at week 4 and −4.87% at week 8 from the baseline. Mild irritation was observed in 10% of the patients at week 4 and self-limited at week 8.…”
Section: Discussionmentioning
confidence: 88%
“…In a series of clinical trials, we have reported clinical efficacy and safety of 0.1% 4nBR cream in the treatment of melasma. In a randomized, double‐blind, vehicle‐controlled, split‐face study, the use of 0.1% 4nBR cream significantly reduced lesional MI compared with control at week 4 and week 8 . Lesional MI decreased by −3.43% at week 4 and −4.87% at week 8 from the baseline.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations